STATISTICAL ANALYSIS OF X-RAY GENERATOR LEAKAGE TEST AT HOSPITALS AND HEALTH CENTERS IN CENTRAL JAVA PROVINCE - Risky Nurseila Karthika; Toto Trikasjono; Supriyono Supriyono (BATAN, 2021)
Several research has been conducted yearly on X-Ray generator leakage by the Research Community and Devotion Polytechnics Institute of Nuclear Technology. However, none have determined the feasibility of X-rays in analyzing radiation leakages. Therefore, this research aims to conduct a statistical analysis test to determine the X-ray generator’s leakage level in radiology installations at several districts in Central Java province, initialized with A, B, C, D, E, F, G, H, and I from 2012-2014. This research was carried out using a non-parametric statistic method due to its ability to analyze data in several places simultaneously at an average radiation leakage value of under 1 mGy/hour. However, some X-Ray Generators at districts H, I, and C exceed the limit of radiation leakage with row percentages of 7.6%, 37.5%, and 14.2%. The condition and information of the ranges in X-Ray Generator leakage at several districts in Central Java can be easily identified because the data is inputted into the thematic map and window chart using the Geographical Information System and computed by ArcView 3.3. The non-parametric statistics results showed that the operating procedure at each radiological installation in some districts of Central Java Province had been conducted in good quality. The data proportion in districts A, B, C, D, E, F, G, H, and I are equal to the statistics values of 2,31033<9,2364; 0,2944442<13,3616; 4,6559925<10,6446; 0,1884249<12,0170; 0,0576894<4,6052; 0,4609793<2,70554; 0,9539133<7,7794; 17,452924<34,3816; 7,2867225<12,0170, respectively.